Yudhoyono to receive UUM honorary doctorate - Borneo Post, (KK) (Borneo Post (kk), 2012)
ALOR SETAR: Indonesian President Dr H Susilo Bambang Yudhoyono will be conferred the Honorary Doctor of Philisophy (Peace Leadership) at a special convocation of Universiti Utara Malaysia (UUM) at Istana Negara today.